Preliminary Study on Aerodynamic Control of High-Angle-of-Attack Slender Body Using Blowing from Penetrating Flow Channels - Ayane Sato; Hiroyuki Nishida; Satoshi Nonaka (International Journal of Aerospace Engineering)
The objective of this study is to experimentally verify a new aerodynamic control concept of a high-angle-of-attack slender body. In the concept, penetrating flow channels are installed to the apex of the slender body. The blowing or suction is generated at the channel exits in response to the surface pressure distribution. First, the effects of the flow channels on the aerodynamic characteristics are experimentally investigated in a low-speed wind tunnel. The result shows the Suction-Blowing type channel is the most effective because its control effect does not reduce even in higher mainstream flow velocity. The peak value of the side force and yawing moment can be reduced by up to 64% and 49%, respectively. In addition, visualization of the surface flow pattern by the oil flow method shows that the Suction-Blowing type channel makes not only the primary separation line on the body side but also the secondary separation line on the body back become symmetric.